Corylin Inhibits Vascular Cell Inflammation, Proliferation and Migration and Reduces Atherosclerosis in ApoE-Deficient Mice - Chen, Chin-Chuan (Antioxidants (Basel), 2020)
Atherosclerosis is a complex disease that includes several events, including reactive oxygen species (ROS) stress, inflammation, endothelial dysfunction, lipid deposition, and vascular smooth muscle cell (VSMC) proliferation and migration, which result in atherosclerotic plaque formation. Corylin, a flavonoid compound, is known to exhibit antioxidative, anti-inflammatory and antiproliferative effects. However, it remains unknown whether corylin could modulate atherogenesis. Here, we identified the anti-inflammatory effect of corylin in tumor necrosis factor-α (TNF-α)-induced vascular cells. In human umbilical vein endothelial cells (HUVECs), corylin suppressed TNF-α-induced monocyte adhesion to the HUVECs and transmigration by downregulating the ROS/JNK/nuclear factor-kappa beta (NF-κB) p65 pathway. In VSMCs, corylin inhibited TNF-α-induced monocyte adhesion by suppressing ROS production, mitogen-activated protein kinase (MAPK) phosphorylation and NF-κB p65 translocation. In platelet-derived growth factor-BB (PDGF-BB)-induced VSMCs, corylin inhibited PDGF-BB-induced VSMC proliferation and migration through regulating the mammalian target of rapamycin (mTOR)/dynamin-1-like protein 1 (Drp1) signaling cascade. In addition, corylin treatment not only attenuated atherosclerotic lesions, ROS production, vascular cell adhesion protein-1 (VCAM-1) expression, monocyte adhesion and VSMC proliferation in apolipoprotein E (ApoE)-deficient mice but also inhibited neointimal hyperplasia in endothelial-denuded mice. Thus, corylin may be a potential prevention and treatment for atherosclerosis.